A new species of Melipriopsis Kirejtshuk, 2011 (Coleoptera: Nitidulidae: Meligethinae) from the Eocene Baltic amber - Kirejtshuk, Alexandr G.; Bukejs, Andris (Zootaxa, 2023)
Melipriopsis baltica sp. nov. is described and illustrated from the Eocene Baltic amber. The described holotype (female) of this species has the fully exposed ovipositor with characters similar (general outline, configuration of lobes of the gonocoxites, and disposition of styli) to those in the extant members of the subfamily Meligethinae.